(untitled) (Modern education and development, 2025)
Hepatitis remains a significant global health concern, affecting millions and posing challenges for healthcare providers. Nurses play a crucial role in managing hepatitis patients by providing clinical care, patient education, and emotional support. This article highlights the importance of hepatitis-related training for nurses, effective nursing interventions, and strategies to improve outcomes for patients with hepatitis A, B, C, and other types.